Guanine nucleotide binding protein-like 3 is a potential prognosis indicator of gastric cancer - Chen, Jing (Int J Clin Exp Pathol, 2015)
Guanine nucleotide binding protein-like 3 (GNL3) is a GIP-binding nuclear protein that has been reported to be involved in various biological processes, including cell proliferation, cellular senescence and tumorigenesis. This study aimed to investigate the expression level of GNL3 in gastric cancer and to evaluate the relationship between its expression and clinical variables and overall survival of gastric cancer patients. The expression level of GNL3 was examined in 89 human gastric cancer samples using immunohistochemistry (IHC) staining. GNL3 in gastric cancer tissues was significantly upregulated compared with paracancerous tissues. GNL3 expression in adjacent non-cancerous tissues was associated with sex and tumor size. Survival analyses showed that GNL3 expression in both gastric cancer and adjacent non-cancerous tissues were not related to overall survival. However, in the subgroup of patients with larger tumor size (≥ 6 cm), a close association was found between GNL3 expression in gastric cancer tissues and overall survival. GNL3-positive patients had a shorter survival than GNL3-negative patients. Our study suggests that GNL3 might play an important role in the progression of gastric cancer and serve as a biomarker for poor prognosis in gastric cancer patients.